Characterizing the Escherichia coli O157:H7 proteome including protein associations with higher order assemblies. - Rembert Pieper; Quanshun Zhang; David J Clark; Shih-Ting Huang; Moo-Jin Suh; John C Braisted; Samuel H Payne; Robert D Fleischmann; Scott N Peterson; Saul Tzipori (PLoS ONE)
Background The recent outbreak of severe infections with Shiga toxin (Stx) producing Escherichia coli (STEC) serotype O104:H4 highlights the need to understand horizontal gene transfer among E. coli strains, identify novel virulence factors and elucidate their pathogenesis. Quantitative shotgun proteomics can contribute to such objectives, allowing insights into the part of the genome translated into proteins and the connectivity of biochemical pathways and higher order assemblies of proteins at the subcellular level. Methodology/principal findings We examined protein profiles in cell lysate fractions of STEC strain 86-24 (serotype O157:H7), following growth in cell culture or bacterial isolation from intestines of infected piglets, in the context of functionally and structurally characterized biochemical pathways of E. coli. Protein solubilization in the presence of Triton X-100, EDTA and high salt was followed by size exclusion chromatography into the approximate M(r) ranges greater than 280 kDa, 280-80 kDa and 80-10 kDa. Peptide mixtures resulting from these and the insoluble fraction were analyzed by quantitative 2D-LC-nESI-MS/MS. Of the 2521 proteins identified at a 1% false discovery rate, representing 47% of all predicted E. coli O157:H7 gene products, the majority of integral membrane proteins were enriched in the high M(r) fraction. Hundreds of proteins were enriched in a M(r) range higher than that predicted for a monomer supporting their participation in protein complexes. The insoluble STEC fraction revealed enrichment of aggregation-prone proteins, including many that are part of large structure/function entities such as the ribosome, cytoskeleton and O-antigen biosynthesis cluster. Significance Nearly all E. coli O157:H7 proteins encoded by prophage regions were expressed at low abundance levels or not detected. Comparative quantitative analyses of proteins from distinct cell lysate fractions allowed us to associate uncharacterized proteins with membrane attachment, potential participation in stable protein complexes, and susceptibility to aggregation as part of larger structural assemblies.